Jerold E. Kemp’s Instructional Design Model in Islamic Religious Education: A Literature-Based Analysis of Its Systematic and Adaptive Features - Husniyah, Bulkis; Rofiq Sofa, Ainur (JSP: Jurnal Studi Pesantren, 2025)
The use of instructional design models in Islamic Religious Education (IRE) requires a framework that connects learning objectives, learner characteristics, instructional materials, learning strategies, media, assessment, and contextual learning conditions. However, existing discussions of Jerold E. Kemp’s model have generally emphasized its components and flexibility without sufficiently synthesizing how its systematic and adaptive features can be understood within IRE. This study examines the relevance of Jerold E. Kemp’s instructional design model to Islamic Religious Education through library research. Data were drawn from relevant books, journal articles, and academic documents discussing instructional design, the Kemp model, and IRE. The data were analyzed using qualitative content analysis and critical-comparative synthesis. The analysis identifies three main findings. First, the Kemp model provides an interconnected design framework that links learning objectives, learner characteristics, content organization, instructional strategies, learning resources, media, assessment, facilities, and time allocation. Second, its non-linear and revisable structure allows instructional planning to respond to variations in learners, content, and educational contexts. Third, its relevance to IRE depends on the alignment between cognitive, affective, and psychomotor objectives and the use of appropriate assessment procedures. The study contributes a literature-based interpretation of the Kemp model by clarifying the conditions under which its systematic and adaptive features may support IRE planning. The findings do not establish empirical effects on student achievement but provide a conceptual basis for further research and instructional development.